Different Outcomes in Two Sexual Abuse Cases due to Different Interpretation of the Same Article - Demirçin, Sema; Sarıkçıoğlu, Süleyman Melik (The Bulletin of Legal Medicine, 2007)
The 6th subsection of article 99 of Turkish Penal Code, brought a new point of view to the termination of pregnancy when is due to a crime.The subsection stated that when performed by the specialist in hospital environment with the approval of the victim, termination of pregnancy not above 20 weeks will not result in punishment of the performer. In this article, 2 of the cases under 18 years of age refered to our department for paternity testing with DNA-STR test were reported. The common feature of the cases was the gestational age above 10 weeks. For both cases termination of the unwanted pregnancy seemed the sole solution. After the pschyiatric evalutiaon of the victims and urgent serial correspondence between physicians and legal authorities the termination of pregnancy was performed for one of the cases. The other case was discharged and given to her family to deliver the unwanted child as the conditions in the law were not provided. Our aim is to point out the discrepancies in interpretation of the law between medical and between legal practitioners and the troubles taking place in practice. Key words: Abortion, termination of pregnancy, sexual abuse, Turkish Penal Code